PENGARUH DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISTEM HIDROLIK SISWA KELAS X TKR SMK NEGERI 3 TONDANO - Yohanes Taduu; David Mapaliey; Jenly Manongko (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
The main purpose of this research is to find out how far the influence of Discovery Learning on Hydraulic System Learning Outcomes on students in SMK Negeri 3 Tondano. On this occasion the researcher used a quasi-experimental approach with a nonrandomized control-group pretest-posttest design. To test the differences in hypotheses with the t-test for data that are normally distributed, the researcher used all students in class X of the TKR Department of SMK Negeri 3 Tondano, totaling 30 students, for the population, while for the sample the researchers divided into two groups, namely the experimental group of 15 students and the experimental group. control 15 students. Based on the results of research conducted that there is a comparison between the values ​​of tcount and ttable, with the acquisition of tcount = 4.22 and ttable = 2.048. For this reason, the value of tcount has more value in the ttable. So, it is said that Ho is not influential while Ha is influential. Therefore, learning Discovery Learning is able to improve hydraulic system learning outcomes for students at SMK Negeri 3 Tondano, especially class X TKR.Keywords: Discovery Learning, Hydraulic System, learning outcomes.